Mathematical model for droplet size prediction of gas-water nozzle based on orthogonal experiment - Xin WANG; Wenpu LI; He SHAO; Yiyi ZHENG; Yurong GAO; Xi CHEN (Meikuang Anquan)
In order to understand the influence of process parameters and structural parameters of internal mixing gas-water nozzle on atomization characteristics, based on a self-designed experimental platform for atomization characteristics, the influence of air supply pressure, water supply pressure, gas-water convergence angle, mixing chamber length and outlet size on atomization characteristics was quantitatively analyzed by orthogonal experiment method, and then a prediction model of nozzle droplet Sauter mean diameter (SMD) was established by using multivariate nonlinear regression method. The experimental results show that the gas flow rate increases with the increase of gas supply pressure, gas-water convergence angle and outlet size, and decreases with the increase of water supply pressure. The water flow rate increases with the increase of water supply pressure and outlet size, and decreases with the increase of water supply pressure and confluence angle. The change of mixing chamber length has no significant effect on gas-water flow. SMD increases with the increase of water supply pressure and outlet size, but decreases with the increase of gas supply pressure, convergence angle and mixing cavity length. The order of the importance of each parameter on nozzle droplet size is outlet size > gas supply pressure > water supply pressure > gas-water convergence angle > mixing cavity length. The calculated values of the multivariate nonlinear prediction model are consistent with the experimental results, and the average relative error is 8.0%, which can be used to predict the droplet size of air atomization nozzle.